AN ANALYSIS OF TRANSLATION STRATEGIES FOUND IN ENGLISH-BAHASA INDONESIA SHORT STORY SOME WORDS WITH A MUMMY - ADNIN, ANNISA NURJANNAH (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: translation, translation strategies, Some Words with a Mummy shortstory. Translation is the process of changing the meaning of the source language text by means of an equivalent target-language text. Translation plays a key role in exchanging the information between languages. The translator should be carefulto use an appropriate strategy to produce a good translation. This study aims tofind out the kinds or translation strategies found in English-Indonesian short storySome Words with a Mummy by using Chesterman’s theory (1997). Furthermore,the writer proposes three problems of the study, (1) What types of translation strategies found in English-Indonesian short story Some Words with a Mummy are(2) What types of translation strategies that most frequently used in English-Indonesian short story Some Words with a Mummy are, and (3) What the possiblereasons the translator uses translation strategies for translating short story SomeWords with a Mummy are. This study used qualitative approaches in document analysis since the data were sentences in a short story. The data source of this study is Some Words with a Mummy short story. The writer applies the theory of Chesterman (1998) whichdivides the classification of translation strategies into three kinds, namely; syntactic strategies, semantic strategies, and pragmatic strategies. From the three kinds of translation strategies, the researcher finds forty five sentences containing translation strategies of Some Words with a Mummy short story. The result shows that nine sentences use syntactic strategies, twenty five sentences use semantic strategies, and eleven sentences use pragmatic strategies. Then, the most frequently used type of translation strategies is a semantic strategies, and the possible reason translator use syntactic strategies is to create the story more natural to reading, next for semantic strategies is to produce the short story clearly understandable to the target language, and for pragmatic strategies is to make the target language understand what is the author’s purpose.The writer suggests the next writer who wants to do the analysis of translation strategies to use another theory or subject.